Health of caregiver-employees in Canada: Determining the value of caregiver-friendly workplace policies and social support - Williams, Allison; Wang, Li; Kitchen, Peter (My University, 2024)
Caregiver-employees (CEs) are working full-time in the labor market while also providing informal/family care to adults. This study provides evidence for the value of carer-friendly workplace policies (CFWPs) in supporting CEs in their paid work. CFWPs were found to support CEs physical health and it can be inferred that CFWPs thereby enable CEs to sustain their dual roles. CFWPs were found to be negatively associated with CE’s unfavorable physical health. CFWPs assist CEs in managing the two demanding roles of unpaid care work and employment.
Keywords: Business and consumer services & culture; Families, households & marital status; Government; Health; Income, pensions, spending & wealth; Labour; Population & demography; Seniors & aging; Society & community